Automatic Program Development - Danvy, O. (Springer, 2017)
Automatic Program Development is a tribute to Robert Paige (1947-1999), our accomplished and respected colleague, and moreover our good friend, whose untimely passing was a loss to our academic and research community. We have collected the revised, updated versions of the papers published in his honor in the Higher-Order and Symbolic Computation Journal in the years 2003 and 2005.